Analisis Perkembangan Kepribadian Sosial Emosiaonal Anak Yang Memiliki Karakter Introvert dan Conduct Disord : Penelitian - Sugiyantoro; Dede Rubai Misbahul Alam (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Every individual is born with different physical and psychological characteristics, resulting in various responses to life situations. The purpose of this study is to provide a comprehensive understanding of the challenges and strategies for social adaptation in introverted children, as well as to identify factors that influence the development of personality and emotional-behavioral disorders in children. This study used a literature review method. The results showed that emotions as an individual's subjective response begin to develop in early childhood, with variations in frequency, intensity, and expression of emotions. Conduct disorders (CD) are characterized by consistent, disproportionate maladaptive behavior and impaired social adaptation function, as well as impulsive characteristics and emotional dysregulation. Children with emotional and behavioral disorders can display internalizing (immaturity, social withdrawal) or externalizing (noncompliance, physical/verbal aggression) behavioral patterns. Introverted personality is characterized by a low need for social stimulation and a tendency to ruminate, which causes difficulties in social adaptation. Various approaches to the treatment of emotional disorders in children have been identified, including behavioral, ecological, socio-cognitive, psychoeducational, psychoanalytic, humanistic, and biogenic. The implication of this study is the emphasis on the need for a holistic and integrated intervention approach in the treatment of emotional and behavioral disorders in children, especially in introverted individuals. An integrative model that combines key elements from various approaches, such as behavioral, cognitive, and biogenic. This shows the importance of individualization of treatment plans, family involvement, and close monitoring of outcomes.